Preliminary Definitions - Dirik, Mahmut; cas, Oscar; Kocamaz, Fatih (Springer Science and Business Media Deutschland GmbH, 2021)
Path planning, localization, and motion control are common problems in mobile robot control. If the working environment is unstructured and unknown, the navigation problem becomes more difficult.